In vivo mitochondrial function in HIV-infected persons treated with contemporary anti-retroviral therapy: a magnetic resonance spectroscopy study. - Brendan A I Payne; Kieren G Hollingsworth; Joanne Baxter; Edmund Wilkins; Vincent Lee; D Ashley Price; Michael Trenell; Patrick F Chinnery (PLoS ONE)
Modern anti-retroviral therapy is highly effective at suppressing viral replication and restoring immune function in HIV-infected persons. However, such individuals show reduced physiological performance and increased frailty compared with age-matched uninfected persons. Contemporary anti-retroviral therapy is thought to be largely free from neuromuscular complications, whereas several anti-retroviral drugs previously in common usage have been associated with mitochondrial toxicity. It has recently been established that patients with prior exposure to such drugs exhibit irreversible cellular and molecular mitochondrial defects. However the functional significance of such damage remains unknown. Here we use phosphorus magnetic resonance spectroscopy ((31)P-MRS) to measure in vivo muscle mitochondrial oxidative function, in patients treated with contemporary anti-retroviral therapy, and compare with biopsy findings (cytochrome c oxidase (COX) histochemistry). We show that dynamic oxidative function (post-exertional ATP (adenosine triphosphate) resynthesis) was largely maintained in the face of mild to moderate COX defects (affecting up to ∼10% of fibers): τ½ ADP (half-life of adenosine diphosphate clearance), HIV-infected 22.1±9.9 s, HIV-uninfected 18.8±4.4 s, p = 0.09. In contrast, HIV-infected patients had a significant derangement of resting state ATP metabolism compared with controls: ADP/ATP ratio, HIV-infected 1.24±0.08×10(-3), HIV-uninfected 1.16±0.05×10(-3), p = 0.001. These observations are broadly reassuring in that they suggest that in vivo mitochondrial function in patients on contemporary anti-retroviral therapy is largely maintained at the whole organ level, despite histochemical (COX) defects within individual cells. Basal energy requirements may nevertheless be increased.